Paradise Destroyed : Catastrophe and Citizenship in the French Caribbean - Church, Christopher M. (Book collections on Project MUSE., 2017)
Over a span of thirty years in the late nineteenth and early twentieth centuries, the French Caribbean islands of Martinique and Guadeloupe endured natural catastrophes from all the elements-earth, wind, fire, and water-as well as a collapsing sugar industry, civil unrest, and political intrigue. These disasters thrust a long history of societal and economic inequities into the public sphere as officials and citizens weighed the importance of social welfare, exploitative economic practices, citizenship rights, racism, and governmental responsibility. Paradise Destroyedexplores the impact of natural and man-made disasters in the turn-of-the-century French Caribbean, examining the social, economic, and political implications of shared citizenship in times of civil unrest. French nationalists projected a fantasy of assimilation onto the Caribbean, where the predominately nonwhite population received full French citizenship and governmental representation. When disaster struck in the faraway French West Indies-whether the whirlwinds of a hurricane or a vast workers' strike-France faced a tempest at home as politicians, journalists, and economists, along with the general population, debated the role of the French state not only in the Antilles but in their own lives as well. Environmental disasters brought to the fore existing racial and social tensions and held to the fire France's ideological convictions of assimilation and citizenship. Christopher M. Church shows how France's "old colonies" laid claim to a definition of tropical French-ness amid the sociopolitical and cultural struggles of a fin de siecle France riddled with social unrest and political divisions.--